Use of image based sports case studies for teaching mechanics - Driscoll, H.; Hart, J.; Allen, T. (Procedia Engineering, 2016)
Mechanics is a fundamental topic required for both undergraduate and postgraduate students on engineering and technology courses. It can be difficult to motivate and engage students in the theoretical aspects of the topic, especially if they are without a strong mathematical background. There are many sporting examples that can be used to explain some of the basic concepts in mechanics. As many sport interactions are high-speed, visualizing the relation to mechanics can be challenging. From our own research, and that published in the field, we now have access to a range of high quality images that have been generated from high-speed video and photogrammetry work, computational simulations or flow visualizations. Two case studies in which images from ball sport research have been used to explain two key engineering subjects: solid and fluid mechanics. A strategy for future collaboration of academics to share and have access to a range of high quality experimental images was also proposed.